1984
DOI: 10.1046/j.1537-2995.1984.24284173340.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and biochemical characteristics of stored red cells preserved with citrate‐phosphate‐dextrose‐adenine‐one and two and prepared from whole blood maintained at 20 to 24 degrees C for eight hours following phlebotomy

Abstract: Studies were conducted to evaluate the characteristics of red cells stored for 35 days following preparation from units of whole blood anticoagulated with citrate-phosphate-dextrose-adenine-one and two (CPDA-1 and CPDA-2) and maintained at 20 to 24 degrees C for 8 hours after phlebotomy. The mean (+/- 1 SD) 24-hour survival for transfused CPDA-1 autologous red cells with hematocrit levels of 78.1 +/- 2.3 percent was 78.0 +/- 8.1 percent (n = 9). The 24-hour survival of red cells from units preserved with CPDA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 16 publications
(1 reference statement)
4
25
0
Order By: Relevance
“…A similar effect of stor age at room temperature has previously been reported in the full-strength citrate anticoagulants CPD.A 1 and CPD.A2, and did not affect in vivo viability [6]. >5.5xl010 platelets in 60±11 ml (n = 6) were stored at 22°C on a 6-rpm circular agitator (Helmer Laboratories).…”
Section: Red Cell Preparationssupporting
confidence: 57%
See 1 more Smart Citation
“…A similar effect of stor age at room temperature has previously been reported in the full-strength citrate anticoagulants CPD.A 1 and CPD.A2, and did not affect in vivo viability [6]. >5.5xl010 platelets in 60±11 ml (n = 6) were stored at 22°C on a 6-rpm circular agitator (Helmer Laboratories).…”
Section: Red Cell Preparationssupporting
confidence: 57%
“…Other workers have already demonstrated that red cell and platelet preparations may be prepared up to 8 [6,[9][10][11][12][13][14][15] or 15 h [ 16] after collection of blood in CPD anti coagulants. The in vitro data presented here indicate that red cell and platelet preparations of good quality may be prepared 18 h after collection in 0.5 CPD.A2.…”
Section: Red Cell Preparationsmentioning
confidence: 99%
“…These recovery and survival studies have been initiated. It has also been shown that red cell and platelet preparations from standard CPD.Al dona tions may be prepared 8-15 h after donation [43][44][45]. It will be of interest to determine if this is also possible for half-strength citrate donations and if so whether the improved stability of Vili : C already demonstrated for blood (table II) and plasma ( fig.…”
Section: Platelet Concentratesmentioning
confidence: 98%
“…This probably reflected the increase in ATP levels which occurred during the holding of whole blood for 8 h at ambient temperature. Such an increase in ATP levels dur ing the holding of units of whole blood has been observed in a number of instances [5][6][7], Red cell 2,3-DPG levels were also slightly better main tained at the lower storage temperature. This was observed when AS-1 red blood cells were stored for 7 days sub sequent to either a 1-or an 8-hour holding time for units of whole blood (table 1).…”
Section: Preparation and Storage Of Red Blood Cellsmentioning
confidence: 59%